TRANSFORMATIONAL PROCESSES IN THE CHURCH CULTURAL AND ADAPTATION SITUATION OF MODERN RUSSIA - Dmitry A. Tsyplakov; Svetlana M. Tsyplakova (Russian Studies in Culture and Society)
Purpose. The work consider the main issue the processes of transformation in church culture. The church adaptation situation in modern Russia is taken as a subject. The authors see necessity on this basis to reveal the features of cultural situation of modern society.